A Novel Biomimetic Wing Design and Optimizing Aerodynamic Performance - Uzun, Metin; Ozdemır, Mustafa; Yıldırım, Çagrı Vakkas (My University, 2022)
In this article, numerical and experimental analyzes were made by adding winglet and endless blade to the tip of the airfoil to improve the wind turbine blade performance. Similarly, the change in performance was investigated by making notches at different sizes and distances on the trailing edge of the wing structure, inspired by the creatures in nature. First of all, the designed wing structures were analyzed by numerical analysis as a fixed wing, and the lift and drag forces were examined and the aerodynamic performance parameters were examined. Then, the winglet, endless wing and trailing edge notch were mounted to the wing structure cast from a 3D printer, and the energy parameters produced by each design in the wind tunnel were examined. In curved wings, the stress values produced depending on the size of the endless wing structure added to the wing tip have changed and up to 15% aerodynamic performance improvement has been observed in the designed wing structure. In addition, the design was experimentally examined on conventional fixed blades, and up to 6% improvement was observed on fixed blades.
Keywords: Aerodynamic; Airfoil; Wind Tunnel; Biomimetic; Wing Design